If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4(x + -2) = 2x + 4 Reorder the terms: 2x + -4(-2 + x) = 2x + 4 2x + (-2 * -4 + x * -4) = 2x + 4 2x + (8 + -4x) = 2x + 4 Reorder the terms: 8 + 2x + -4x = 2x + 4 Combine like terms: 2x + -4x = -2x 8 + -2x = 2x + 4 Reorder the terms: 8 + -2x = 4 + 2x Solving 8 + -2x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + -2x + -2x = 4 + 2x + -2x Combine like terms: -2x + -2x = -4x 8 + -4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + -4x = 4 + 0 8 + -4x = 4 Add '-8' to each side of the equation. 8 + -8 + -4x = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -4x = 4 + -8 -4x = 4 + -8 Combine like terms: 4 + -8 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 12m^2+37m-10=0 | | (3x-18)+2x+x=180 | | 60r-50=15r | | x^2-11=4x | | 2m^2+6m+1m+6=0 | | 6.28=3.14x | | 4x-20+30=2x | | (2x-8)+90=180 | | 10(324)+14K= | | 8y+44=4y | | 10(243)+14K= | | 2m^2+7m+6=0 | | 3=-16t^2+4t | | (3x+51)+37+x=180 | | T+K=243 | | 2x-10=25 | | 650+30(n-10)= | | 3/4(m-6)=-2 | | 3/4(m-6)=2 | | 1x^2+1+1x^2=5 | | m^2+20m-300=0 | | 1.5y=6 | | n+4N=245 | | k^2-13k+12=0 | | -3p+7=5-(5p+7) | | (3)2X+3Y=75.75 | | (-2)3X+2Y=79.40 | | 174=15x+4X^2 | | -3x-2y-x-5xy+3= | | 6.4+7x(2)=10.9-6x | | 3S+2J=75.78 | | -2x+4=7x-3 |